FTIR SPECTRUM COMPARISON OF PLANTS purgatives [ ALOE VERA LINNEO . ALOE BARBADENSIS MILLER , RHEUM PALMATUM ( Rhubarb ) , RHAMNUS Pursiana ( SACRED SHELL ) AND CASSIA SP. (SEN )] - Saavedra N., F. (2011)
FTIR identified the carbonyl C = O functional group of the anthraquinone derivatives in aqueous macerated and alcoholics purges as aloe plants (Aloe vera L. , Aloe barbadensis Miller ) , senna ( Cassia spp . ) , Rhubarb ( Rheum palmatum) and shell sagrada (Rhamnus Pursiana ) without prior separation of the components by chromatographic methods or other physical and chemical methods . We show that the absorption maxima for the C = O carbonyl group of the anthraquinone derivatives in aqueous and alcoholic macerated Aloe vera and Aloe barbadensis L. Miller- interact with inorganic salts - for a week , as time passes, these maxima moving to higher-frequency areas . This procedure can be recommended for detection of anthraquinone derivatives in encapsulated pharmaceutical preparations and extracts of the plants mentioned purgatives